2016
DOI: 10.1080/23311886.2016.1191322
|View full text |Cite
|
Sign up to set email alerts
|

Law enforcement disconnect from the community

LisaAnn Gittner

Abstract: The dialog about enforcing the law varies between administrators, politicians, law enforcement officers, and the community. Each in turn has their own defined language. We performed a qualitative study on how officers reported critical incidents. A convenience sample of Louisiana and Mississippi Police officers was recruited from the Regional Counterdrug Training Academy in Meridian, MS. All participants were rural law enforcement officers (n = 307).Officers answered qualitative open-ended questions about thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Fortunately, there was a monument built to remember the victims at the last-mentioned place, although it was built by local people, not the government. The community became another victim, who was being detached from the valid law enforcement, which possibly resulted in continuous trauma (Gittner, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, there was a monument built to remember the victims at the last-mentioned place, although it was built by local people, not the government. The community became another victim, who was being detached from the valid law enforcement, which possibly resulted in continuous trauma (Gittner, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…PSWs may even improve relations between police departments and their communities, especially in cases where interactions have been shaped by distrust, historical discrimination, and violence. Trust between communities and police departments is susceptible to damage if community members feel disrespected or misunderstood by police officers (Gittner & Chamberlain, 2016). PSWs can bring positive change to communities by improving the relationship between community members and police officers (Vanhanen & Heikkilä, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their sample showed the benefits of creating a positive image for the department with the followers on one social media platform. A qualitative study by Gittner (2016) demonstrated that occupational language use by police officers disengages them from the stress of their work. However, this same language often disconnects the police from the public.…”
mentioning
confidence: 99%